Compiling and Using Export and Import Price Indices - Zieschang, Kimberly (IMF Working Papers; Working Paper ;, 2002)
Export and import price indices are essential for assessing the impact of international trade on the domestic economy. Among their most important uses are analyzing developments in the trade balance, measuring foreign prices' contribution to domestic inflation, and deflating nominal values of exports and imports for estimating the volume of gross domestic product. This paper discusses the main uses of trade indices and the data sources used to compile them. It also presents various approaches used to compile foreign trade price indices, addresses various problems encountered in developing these indices, and provides some recommendations on how to address them.